2018
DOI: 10.1108/jiabr-10-2017-0146
|View full text |Cite
|
Sign up to set email alerts
|

Does prospectus information matter in IPO pricing?

Abstract: Purpose The purpose of this study is to identify selected information from the prospectus that might signal the initial public offering (IPO) offer price. Design/methodology/approach This study uses cross-sectional data for a 14-year period from 2000 to 2014 in examining hypotheses relating to Shariah-compliant status, institutional investors, underwriter ranking and shareholder retention, with respect to their associations with the offer price of the IPOs. Further, this study uses ordinary least squares (OL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 29 publications
6
26
1
Order By: Relevance
“…Underwriters set offer prices below the market equilibrium to allure investors to subscribe to IPOs and to reduce the likelihood of having to absorb losses for unsold shares. The negative result is consistent with Mohd-Rashid et al (2018), which found that prestigious underwriters priced IPOs lower to attract investors into the IPO market. In the emerging market environment, issuers spend huge amounts to hire prestigious underwriters to certify firms that have greater risks.…”
Section: Regression Results Between Underwriter Reputation and Ipo Valuationsupporting
confidence: 85%
See 2 more Smart Citations
“…Underwriters set offer prices below the market equilibrium to allure investors to subscribe to IPOs and to reduce the likelihood of having to absorb losses for unsold shares. The negative result is consistent with Mohd-Rashid et al (2018), which found that prestigious underwriters priced IPOs lower to attract investors into the IPO market. In the emerging market environment, issuers spend huge amounts to hire prestigious underwriters to certify firms that have greater risks.…”
Section: Regression Results Between Underwriter Reputation and Ipo Valuationsupporting
confidence: 85%
“…The OLS results showed that underwriter reputation had a significant negative association with IPO valuation. This study confirms the findings of a prior study by Mohd-Rashid et al (2018), which found reputable underwriters set offer prices lower than firms' intrinsic values to reduce the probability of having to repurchase unsold IPO shares. Nevertheless, the certification of IPOs seemed to be influenced by information asymmetry, which in turn reduced firms' values in the immediate aftermarket.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the context of the Malaysian IPO market that is riddled with severe uncertainties, underwriters and issuers always set lower fixed-price IPOs offer prices to allure investors for shares subscription (Mohd-Rashid et al 2018). The credible signals of IPOs with greater growth opportunities drive investors' demands on shares (Vong 2006;McGuinness 2019) and the demands propel aftermarket prices during the first trading of IPOs.…”
Section: Resultsmentioning
confidence: 99%
“…The final offer price of Malaysian IPOs is subject to the approval of the Securities Commission (SC) in ensuring the IPO price is determined on a fair value basis (Abdul-Rahim & Yong 2010). Indeed, the offer price is set below the share prices of IPOs (Mohd-Rashid et al 2018;Yong 2015). This is due to the existence of information asymmetry problem between issuers and potential investors as the private information on actual values of firms are not incorporated into the offer prices.…”
Section: Introductionmentioning
confidence: 99%